Pengaruh Model Discovery Learning dengan Media Video Animasi terhadap Pemahaman Konsep IPAS Siswa Kelas III pada Materi Sumber Energi di Sekitar Kita di SDN 1 Aikmel - Lilis Rizkiya Amanda; Muhammad Tahir; Ni Made Yeni Suranti (Mataram University, 2026)
The low level of conceptual understanding in IPAS learning among third-grade elementary school students remains a significant challenge, especially on the topic of energy sources in the surrounding environment. This study aimed to examine the effect of the Discovery Learning model assisted by animated video media on students’ conceptual understanding. The research employed a quantitative approach with a quasi-experimental design involving an experimental class and a control class. Data were collected using pretest and posttest instruments administered to both groups. The experimental class received instruction through the Discovery Learning model integrated with animated video media, while the control class was taught using conventional learning methods. The findings revealed that the average score of the experimental class increased significantly from 24.81 in the pretest to 81.71 in the posttest. Meanwhile, the control class showed an increase from 25.84 to 69.56. The results indicate that students in the experimental class experienced greater improvement in conceptual understanding compared to those in the control class. Therefore, the application of the Discovery Learning model assisted by animated video media was proven effective in improving students’ conceptual understanding in IPAS learning, particularly on the topic of energy sources in the surrounding environment.